2020
DOI: 10.3390/ma13194257
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Contact Conductance-Based Thermal Behavior Analytical Model for a Hybrid Floor at Elevated Temperatures

Abstract: Hybrid floors infilled with polymeric materials between two steel plates were developed as a prefabricated floor system in the construction industry. However, the floor’s fire resistance performance has not been investigated. To evaluate this, fire tests suggested by the Korean Standards should be performed. As these tests are costly and time consuming, the number of variables were limited. However, many variables can be investigated in other ways such as furnace tests and finite element analysis (FEA) with le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…The contact surfaces between two materials are related to physical factors, such that the thermal contact conductance at elevated temperatures can be altered by physical properties such as residual mass. The residual mass at elevated temperatures can be obtained from thermal gravimetric analysis (TGA) obtained from previous study [11], as shown in Figure 2. The reduction ratio of thermal contact conductance at elevated temperatures agrees with the pattern of the TGA results, and the value of the thermal contact conductance at ambient temperatures is 250 W/m 2 such that the thermal contact conductance at elevated temperatures can be altered by physical properties such as residual mass.…”
Section: Thermal Behavior Analytical Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…The contact surfaces between two materials are related to physical factors, such that the thermal contact conductance at elevated temperatures can be altered by physical properties such as residual mass. The residual mass at elevated temperatures can be obtained from thermal gravimetric analysis (TGA) obtained from previous study [11], as shown in Figure 2. The reduction ratio of thermal contact conductance at elevated temperatures agrees with the pattern of the TGA results, and the value of the thermal contact conductance at ambient temperatures is 250 W/m 2 such that the thermal contact conductance at elevated temperatures can be altered by physical properties such as residual mass.…”
Section: Thermal Behavior Analytical Modelmentioning
confidence: 99%
“…Owing to this feature, polymers, which are elastomers that have large failure strains on the composite floors, were targeted to exhibit strong bond strengths in the early development stage. To investigate the fire resistance performance of composite floors, fire-resistant polymers have been developed, thus enhancing fire resistance [11]. However, conducting fire tests based on Korean Standards (KS) was very difficult in Korea [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations